Alpha‐Lipoic Acid Alleviates Acute Inflammation and Promotes Lipid Mobilization During the Inflammatory Response in White Adipose Tissue of Mice. Issue 10 (16th August 2016) - Guo, Jun; Gao, Shixing; Liu, Zhiqing; Zhao, Ruqian; Yang, Xiaojing
Abstract: Recently, white adipose tissue has been shown to exhibit immunological activity, and may play an important role in host defense and protection against bacterial infection. Αlpha‐lipoic acid (α‐LA) has been demonstrated to function as an anti‐inflammatory and anti‐oxidant agent. However, its influence on the inflammatory response and metabolic changes in white adipose tissue remains unknown. We used male C57BL/6 mice as models to study the effect of α‐LA on the inflammatory response and metabolic changes in white adipose tissue after stimulation with lipopolysaccharide (LPS). The non‐esterified fatty acid content was measured by an automatic biochemical analyzer. The expression of inflammation‐, lipid‐ and energy metabolism‐related genes and proteins was determined by quantitative real‐time polymerase chain reaction and western blotting. The results indicated that α‐LA significantly decreased the epididymis fat weight index and the non‐esterified fatty acid content in plasma compared with the control group. LPS significantly increased the expression of inflammation genes and α‐LA reduced their expression. The LPS‐induced expression of nuclear factor‐κB protein was decreased by α‐LA. Regarding lipid metabolism, α‐LA significantly counteracted the inhibitory effects of LPS on the expression of hormone‐sensitive lipase gene and protein. α‐LA evidently increased the gene expression of fatty acid transport protein 1 and cluster of differentiation 36. Regarding energy metabolism, α‐LA significantly increased the expression of most of mitochondrial DNA‐encoded genes compared with the control and LPS group. Accordingly, α‐LA can alleviate acute inflammatory response and this action may be related with the promotion of lipid mobilization in white adipose tissue.